EVALUASI PENERAPAN MODERASI BERAGAMA TERHADAP SIKAP BERAGAMA PESERTA DIDIK DI SMP PGRI KECAMATAN NGRAHO KABUPATEN BOJONEGORO - Siti Almaratus Sholikah (Evaluasi: Jurnal Manajemen Pendidikan Islam, 2022)
Abstract. Religious moderation is very important in a homogeneous country, such as Indonesia, which is rich in diversity, so it is very easy to create friction between groups, especially between religions. Thisi studyi uses a descriptivei qualitativei researchi approach, with primary data sources being principals, teachers and students while secondary data sources in the form of documents, photos of school archives, in collecting data the researchers used three ways, namely: participatory interviews, non-structured interviews and documents, whilei datai analysisi through:idata collection, data condensation, data displayi and drawingi iconclusions. The results of this research are: Planning for religious moderation on the religious attitudes of students at SMP PGRI Ngraho District, Bojonegoro Regency includes: Student selection, Indoctrination includes: noble character, and have competitiveness, Instrumentation includes: written and well structured practice The application of religious moderation to the religious attitudes of students at SMP PGRI Ngraho District, Bojonegoro Regency includes: tolerance, not group fanatics, respecting culture, prioritizing unity. carried out well. Evaluation of religious moderation on the religious attitudes of students at SMP PGRI Ngraho District, Bojonegoro Regency includes: changes in attitudes, improving knowledge and increasing skills. Supporting factors and obstacles to the application of religious moderation on students' religious attitudes at SMP PGRI Ngraho District, Bojonegoro Regency as the following: the role of the principal, student support, student input. written and well structured practice The application of religious moderation to the religious attitudes of students at SMP PGRI Ngraho District, Bojonegoro Regency includes: tolerance, not group fanaticism, respecting culture, promoting unity. carried out well. Evaluation of religious moderation on the religious attitudes of students at SMP PGRI Ngraho District, Bojonegoro Regency includes: changes in attitudes, improving knowledge and increasing skills. Supporting factors and obstacles to the application of religious moderation on students' religious attitudes at SMP PGRI Ngraho District, Bojonegoro Regency as the following: the role of the principal, student support, student input. written and well structured practice The application of religious moderation to the religious attitudes of students at SMP PGRI Ngraho District, Bojonegoro Regency includes: tolerance, not group fanaticism, respecting culture, promoting unity. carried out well. Evaluation of religious moderation on the religious attitudes of students at SMP PGRI Ngraho District, Bojonegoro Regency includes: changes in attitudes, improving knowledge and increasing skills. Supporting factors and obstacles to the application of religious moderation on students' religious attitudes at SMP PGRI Ngraho District, Bojonegoro Regency as the following: the role of the principal, student support, student input. respecting culture, prioritizing unity. carried out well. Evaluation of religious moderation on the religious attitudes of students at SMP PGRI Ngraho District, Bojonegoro Regency includes: changes in attitudes, improving knowledge and increasing skills. Supporting factors and obstacles to the application of religious moderation on students' religious attitudes at SMP PGRI Ngraho District, Bojonegoro Regency as the following: the role of the principal, student support, student input. respecting culture, prioritizing unity. carried out well. Evaluation of religious moderation on the religious attitudes of students at SMP PGRI Ngraho District, Bojonegoro Regency includes: changes in attitudes, improving knowledge and increasing skills. Supporting factors and obstacles to the application of religious moderation on students' religious attitudes at SMP PGRI Ngraho District, Bojonegoro Regency as the following: the role of the principal, student support, student input.